SPREADING RELIGION AND CULTURE THROUGH INTERNET MEMES - Navrang Rathi and Pooja Jain (Journal of Dharma, 2024)
This paper delves into the use of Internet memes as a means of spreading religion and ethical values in modern society. With the rise of the Internet and social media, memes have gained popularity as a form of shared content with the ability to convey meaningful messages. The research evaluates the prevalence and impact of memes in religious and ethical contexts. Through this research, the authors present their viewpoint after mulling over the findings of authors like Limor Shifman. The study asserts that memes can facilitate discussions, promote religious literacy, reinforce beliefs, and instil ethical values. Additionally, it anticipates that religious and ethical memes may influence individuals' actions in their daily lives. This research is significant as it examines the potential of memes to serve as a contemporary tool for spreading religion and ethics in a digital world.